High‐resolution positron emission tomography/computed tomography imaging of the mouse heart. Issue 3 (28th November 2012) - Greco, Adelaide; Fiumara, Giovanni; Gargiulo, Sara; Gramanzini, Matteo; Brunetti, Arturo; Cuocolo, Alberto
Abstract : Different animal models have been used to reproduce coronary heart disease, but in recent years mice have become the animals of choice, because of their short life cycle and the possibility of genetic manipulation. Various techniques are currently used for cardiovascular imaging in mice, including high‐resolution ultrasound, X‐ray computed tomography (CT), magnetic resonance imaging and nuclear medicine procedures. In particular, molecular imaging with cardiac positron emission tomography (PET) allows non‐invasive evaluation of changes in myocardial perfusion, metabolism, apoptosis, inflammation and gene expression or measurement of changes in left ventricular functional parameters. With technological advances, dedicated small laboratory PET/CT imaging has emerged in cardiovascular research, providing in vivo a non‐invasive, serial and quantitative assessment of left ventricular function, myocardial perfusion and metabolism at a molecular level. This non‐invasive methodology might be useful in longitudinal studies to monitor cardiac biochemical parameters and might facilitate studies to assess the effect of different interventions after acute myocardial ischaemia.